Comparison of immunohistochemical characteristics of prognostic markers expression in non-metastatic and metastatic invasive endometrioid endometrial carcinoma - A. V. Chepets (Zaporožskij Medicinskij Žurnal)
Endometrial cancer occupies the sixth place among oncological morbidity structure in women worldwide.